Physical Characteristics of Three Types of Muscles with Different Aging Times - K. D. Yulianti; R. Priyanto; H. Nuraini (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2023)
The demand for premium beef continues to increase along with changes in the lifestyle of upper middle class, increasing tourists and expatriates from abroad. Local cattle usually cannot produce premium beef, but aging can improve the quality of meat. This study aimed to characterize the physical quality (pH, cooking loss, water holding capacity, and tenderness) of bali beef with different aging times. This study used three types of muscles, which is Longissimus dorsi, Gluteus medius, and Semitendinosus from bali beef aged ± 3 years and body weight of ± 350 kg. Samples were aged at cold temperatures for 1, 21, and 42 days. A completely randomized design with a 3x3x4 factorial was used in this study. Least Square Means test was applied if the data obtained is significantly different. The results showed that the three types of muscle produced relatively the same physical properties, except for cooking loss. The Longissimus dorsi and Semitendinosus muscles were aged for 21 days to show the best results ofmeat tenderness.